Inflammation and intestinal metaplasia of the distal esophagus are associated with alterations in the microbiome - Yang, Liying (2009)
BACKGROUND & AIMS: Gastroesophageal reflux causes inflammation, intestinal metaplasia and its downstream sequelum adenocarcinoma in the distal esophagus. The incidence of esophageal adenocarcinoma has increased approximately 6-fold in the U.S. since the 1970s, accompanied with a significant increase in prevalence of gastroesophageal reflux disease (GERD). Despite extensive epidemiological study, the cause for GERD and the unexpected increases remain unexplainable. Microbes are among the environmental factors that may contribute to the etiology of GERD but very little research has been done on the esophageal microbiome, particularly in its relation to GERD. This is the first reported correlation between a change in the esophageal microbiome and esophageal diseases. METHODS: Biopsies of the distal esophagus were collected from 34 patients. Host phenotypes were histologically defined as normal, esophagitis, or Barrett’s esophagus (intestinal metaplasia). Microbiomes from the biopsies were analyzed by bacterial 16S rRNA gene survey and classified into types using unsupervised cluster analysis and phenotype-guided analyses. Independence between host phenotypes and microbiome types were analyzed by Fisher Exact test. RESULTS: Esophageal microbiomes can be classified into two types. The type I microbiome was dominated by the genus Streptococcus and concentrated in the phenotypically normal esophagus. Conversely, the type II microbiome contained a greater proportion of Gram-negative anaerobes/microaerophiles and primarily correlated with esophagitis (Odds Ratio: 15.4) and BE (Odds Ratio: 16.5). CONCLUSIONS: In the human distal esophagus, inflammation and intestinal metaplasia are associated with global alteration of the microbiome. These findings raise the issue of a possible role for dysbiosis in the pathogenesis of reflux-related disorders.